Microsoft Exchange server 2003 deployment and migration SP1 and SP2 - McCorry, Kieran, 1968- (Burlinton, MA : Elsevier Digital Press, 2006)
Exchange Server is necessary to support Outlook and SharePoint in the enterprise messaging at virtually all Fortune 1000 firms. Microsoft(r) Exchange Server 2003 SP1 and SP2 Deployment and Migration describes everything that you need to know about designing, planning, and implementing an Exchange 2003 environment. This book covers, in detail, the tools and techniques that messaging system planners and administrators will require in order to establish a functioning interoperability environment between Exchange 2003 and previous versions of Exchange including Exchange 5.5 and Exchange 2000. The book describes various deployment topologies and environments to cater for a multitude of different organizational requirements. The book has been updated to reflect the new changes that Microsoft introduced with Exchange 2003 and SP1 and SP2 updates in relation to major architectural changes to migrations techniques and other services such as RPC over HTTP and journaling functionality. * Details for consultants and system administrators to migrate from older versions of Exchange 5.5 and Exchange 2000 to the latest revisions of Exchange 2003 * Critical information on integration with Office 2003 and Windows 2003 * Based on actual implementations of the released version of Exchange 2003 in larger enterprise environments * NEW! Cover critical updates to Exchange 2003 with updates from SP1 and SP2, such as new implementations of RPC over HTTP and cross site migrations * NEW! Coverage of the Exchange journaling feature updates in Exchange 2003 SP1 and SP2.
1. Introducing Exchange Server 2003 -- 2. Exchange Server 2003 Deployment Basics -- 3. The Active Directory Connector -- 4. Exchange Server 2003 Migration -- 5. Exchange Server 2003 OWA Deployment -- 6. Exchange Server 2003 RPC over HTTP Deployment -- 7. Exchange Server 2003 Datacenter Deployment.
Includes index.
"Since the publication of 'Microsoft Exchange server 2003 deployment and migration', I have gathered suitably new content and have included it in this updated version of the book ... [which] coincided nicely with the substantive changes that Microsoft has introduced with Service Packs 1 and 2 for Exchange 2003"--Pref.
Keywords: Microsoft Exchange server; Client/server computing; Electronic mail systems; Electronic books